Revisiting the Effects of Gender Diversity in Small Groups on Divergent Thinking: A Large-Scale Study Using Synchronous Electronic Brainstorming - Peter, Laurine; Michinov, Nicolas; Besançon, Maud; Michinov, Estelle; Juhel, Jacques; Brown, Genavee; Jamet, Eric; Cherbonnier, Anthony; , ProFAN Consortium; Anatolia, Batruch; Fabrizio, Butera; , Desrichard Olivier; et al. (Frontiers in Psychology, 2021)
Numerous studies have examined the effects of gender diversity in groups on creative performance, and no clear effect has been identified. Findings depend on situational cues making gender diversity more or less salient in groups. A large-scale study on two cohorts (N = 2,261) was conducted among business students to examine the impact of the gender diversity in small groups on creative performance in an idea-generation task performed by synchronous electronic brainstorming. Participants were automatically randomized in three- or four-member groups to generate ideas during ten minutes on a gendered or neutral task. Then, five categories of groups where the proportion of men/women in groups varied from three/four men to three/four women were compared to examine creative performance on three divergent thinking measures (fluency, flexibility, and originality). A Multivariate Generalized Linear Mixed Model (mGLMM) showed a greater fluency in all-women groups than in other groups, and more specifically ‘solo’ groups composed of a single woman/man among a majority of men/women. For flexibility and originality, the superiority of all-women groups was found only in comparison to ‘solo’ groups composed of a single woman. As gender differences are more salient in ‘solo' groups than in other groups faultlines may appear in groups, leading to a deleterious impact on creative performance.